Understanding the Election Results in Portugal. A spatial econometrics point of view - António Caleiro; Gertrudes Guerreiro (Universidade de Évora, Departamento de Economia, 2003)
The great majority of the theoretical analysis about electoral cycles has considered the national space as the territory of interest for the study of the economic consequences of an electoralist behaviour by the central government. This fact, in conjunction to the nature of the data most commonly available, has lead many authors to empirical studies which, by the use of more or less sophisticated econometric techniques, intend to verify the empirical evidence of electoral cycles whether in their political versions or in their partisan versions. Given that the election results for the main parties, at least for Portugal, clearly reflect some spatial localization we find rather intriguing to verify that so very few of those empirical studies use spatial econometrics techniques. This being said, the main objective of the paper is to analyse the results corresponding to the last legislative election that took place in Portugal, from the partisan viewpoint, by the use of well-known techniques of spatial econometrics. The confrontation of the results with the ones obtained ignoring the spatial localization of the data will lead us to the nature and extent of the improvement on the results obtained by spatial econometrics techniques in what concerns the detection of empirical evidence supporting the existence of a link between voters' ideology and the election results obtained by the two main parties in Portugal.
http://hdl.handle.net/10174/8406
Keywords: C31; E32; R12; 330; Elections; Partisan Models; Portugal; Spatial Econometrics; Voters